Impact of Factors Related to Loose and Pouched Moist Smokeless Tobacco Product Use Behavior on Biomarkers of Exposure to Nicotine and N-Nitrosonornicotine - Webb Katy M.; Scott Rensch J.; Wang Jingzhu; Jin Xiaohong; Edmiston Jeffery S.; Sarkar Mohamadi (Contributions to Tobacco and Nicotine Research)
Use behavior of loose or pouched moist smokeless tobacco (MST) products and its impact on biomarkers of exposure (BOE), specifically nicotine (nicotine equivalents; NE) and N-nitrosonornicotine (NNN), have not been well characterized.